Faerie after - Simner, Janni Lee. (New York : Random House Children's Books, 2013)
Liza must journey to the Faerie realm in order to save both the fairy and human worlds from impending doom.
Sequel to: Faerie winter.
Keywords: Fairies -- Fiction; Magic -- Fiction; Coming of age -- Fiction